Pemetaan Pengelolaan Keuangan, Komunikasi dan Budaya dalam Pemasaran Produk di Kampung Batik Semarang - Lenny Setyowati; Ekawati Marhaenny Marhaenny Dukut; Devitia Putri Nilamsari (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2023)
In Indonesia, batik is popular in every area. Specifically, on the island of Java, batik that comes from Yogyakarta, Pekalongan, Surakarta, and Lasem, have emerged as Batik Yogya, Batik Pekalongan, Batik Surakarta, Batik Cirebon, and Batik Lashem. It is interesting to note that not many people have heard of Batik Semarangan, even though Semarang city is the capital of Central Java. Thus, the popularity of Batik Semarang needs to be raised to gain publicity. The purpose of doing research on Batik Semarangan is (1) to analyze the financial management of Kampung Batik, (2) to see how effective the financial management is on marketing through Integrated Marketing Communication (IMC), and (3) to map out the cultural wealth around Semarang city that is shown through the Batik Semarangan cloth motifs. Instruments utilized in the research are questionnaires and interviews with Batik designers. The research finds that (1) good financial management will direct regular financial governance that can allocate funds for operational, payday, or marketing interests, (2) the IMC strategy is appropriate for the cultural promotion of the batik village, and (3) the unique motifs depicting Semarang city’s architecture and flora and fauna prove to assist in today's digital promotion of Batik Semarangan that can penetrate the borders of any country. Keywords: Batik Semarangan, financial management, cultural communication, IMC